Novel 3-dimensional effective regurgitation orifice area quantification serves as a reliable tool to identify severe mitral valve regurgitation - Tobias Harm; Frederic-Joaquim Schwarz; Monika Zdanyte; Andreas Goldschmied; Livia Baas; Parwez Aidery; Serhii Shcherbyna; Ioannis Toskas; Timea Keller; Isabela Kast; Juergen Schreieck; Tobias Geisler; et al. (Scientific Reports, 2024)
Abstract A precise quantification of mitral regurgitation (MR) severity is essential for treatment and outcome of patients with MR. 3D echocardiography facilitates estimation of MR but selection of patients with necessity of invasive treatment remains challenging. We investigate effective regurgitation orifice area (EROA) quantification by 3D compared to 2D echocardiography in patients with MR and highlight the improved discrimination of MR severity. We consecutively enrolled fifty patients with primary or secondary and at least moderate MR undergoing 2D and 3D colour Doppler echocardiography prior to transcatheter edge-to-edge repair (TEER). Improved accuracy of MR grading using 3D vena contracta area (VCA) as an estimate of EROA was compared to 2D proximal isovelocity surface area (PISA) quantification method and a multiparameter reference standard. Quantification of EROA remarkably varies between 2D and 3D echocardiography and the discrimination between moderate and severe MR was significantly (p = 0.001) different using 2D PISA or 3D VCA, respectively. 3D VCA correlated significantly (r = 0.501, p < 0.001) better with the pre-defined MR severity. We detected crucial differences in the correct identification of severe MR between 2D and 3D techniques, thus 2D PISA significantly (p < 0.0001) underestimates EROA due to clinical and morphological parameters. The assessment of 3D VCA resulted in improved diagnostic accuracy.